AN EVALUATION OF FACTORS AFFECTING THE DEVELOPMENT OF HUMAN RESOURCES IN HUNG YEN GARMENT ENTERPRISES - Nguyen Quoc Phong; Nguyen Thi Minh Ngoc (Journal of Applied Science and Technology, 2019)
The garment enterprises gradually increase their roles in the local economic development, especially the issue of job creation opportunities. To contribute to the development of human resources in the garment industry, the authors conduct research to assess the impacts affecting the human resource development in garment enterprises in Hung Yen through internal and external factors and employees themselves. From t he synthesis of the previous studies, the paper proposes a research model, conducting quantitative research to analyze the impacts of factors on human development and give some suggestions for developing human resources in garment enterprises in Hung Yen in the coming time.